Real Impact and Shared Value: Palm Sustainability in Colombia 2025 - Federación de Cultivadores de Palma de Aceite, Fedepalma (Fedepalma, 2026)
This infographic briefly presents the achievements in palm oil sustainability for the year 2025
Palm Sustainability in Colombia 2025
Keywords: Sustainability; palm sector; production; economic performance; environmental performance; social performance; agroecosystems; fuels; aviation; palm oil; Colombia.